Somatic Embryogenesis Induction in Narcissus papyraceus cv. Shirazi - Anbari, Saghi; Tohidfar, Mosoud; Hosseini, Ramin; Haddad, Rahim (Plant Tissue Culture and Biotechnology, 2008)
Explants from bulb scales of Narcissus papyraceus cv. Shirazi cultured in MS and Nitsch media containing different concentrations of BAP, 2,4-D, GA3, Kn, IBA and NAA produced highest number of regenerated bulblets in Nitsch medium containing BAP (2.2 mg/l) and 1.1 mg/l 2,4-D. The highest number of direct somatic embryos were observed in MS containing 0.5 mg/l GA3, 1.6 mg/l BAP and 1.6 mg/l 2,4-D. Induced somatic embryos were multiplied by transferring them to hormone free MS. Key words: Narcissus, Somatic embryogenesis, Regeneration DOI = 10.3329/ptcb.v17i1.1119 Plant Tissue Cult. & Biotech. 17(1): 37-46, 2007 (June)